Treatment of bleeding from a portion of pancreatojejunostomy after pancreaticoduodenectomy with division of the splenic vein: two case reports - Hiroki Kushiya; Takehiro Noji; Daisuke Abo; Takeshi Soyama; Kimitaka Tanaka; Yoshitsugu Nakanishi; Toshimichi Asano; Toru Nakamura; Takahiro Tsuchikawa; Keisuke Okamura; Satoshi Hirano (Surgical Case Reports)
Abstract Background There is no definitive strategy for gastrointestinal bleeding due to left-sided portal hypertension after pancreaticoduodenectomy (PD) for pancreatic cancer (PC) with concomitant portal vein resection (PVR). Case presentation Case 1: A 70-year-old woman underwent a PD for PC with PVR. Seven years after her surgery, she suffered severe anemia with suspected gastrointestinal bleeding. Computed tomography scan (CT) revealed varices at a portion of the pancreaticojejunostomy (PJ). Angiography revealed that splenic venous flow drained into the varices and then into the portal vein. A diagnosis of bleeding varices of the PJ due to left-sided portal hypertension was made. Following a partial splenic artery embolization, her anemia improved. Case 2: An 80-year-old male underwent a PD for pancreatic head cancer combined with resection of the confluence of the portal and splenic veins with a reconstruction between the portal and superior mesenteric veins. Eighteen months after his surgery, he developed melena with negative endoscopy findings in his large and small bowel. CT revealed varices at the site of the PJ that communicated with the jejunal and portal veins. He underwent obliteration of the varices via a trans-portal-venous approach. As a result, he remained without melena until he died of PC 17 months after the embolization. Conclusions Left-sided portal hypertension following a PD with bleeding varices can be treated by interventional radiology with minimal invasiveness.